1984
DOI: 10.1111/j.1365-2125.1984.tb02452.x
|View full text |Cite
|
Sign up to set email alerts
|

Omeprazole: effects on oxidative drug metabolism.

Abstract: Omeprazole, a substituted benzimidazole, and a potent inhibitor of gastric parietal cell H+/K+ ATPase, was tested for drug interactions at two dose levels (30 mg and 60 mg/day) in man using the model drugs [14C]‐aminopyrine and antipyrine. Elimination of both models was assessed before and after 15 days treatment with omeprazole. In addition [14C]‐aminopyrine metabolism was assessed on day 2 of treatment to investigate the rapidity of onset of any effect. In 10 healthy male volunteers omeprazole 60 mg/day for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
2

Year Published

1985
1985
1994
1994

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(19 citation statements)
references
References 12 publications
0
17
2
Order By: Relevance
“…Previous work, however, suggests that omeprazole could significantly interfere with the hepatic elimination of phenytoin: omeprazole 60 mg day-' impairs antipyrine clearance by 14%, although no significant change occurs with a lower dose (30 mg day-1) (Henry et al, 1984); and omeprazole (40 mg day-1) decreases the clearance of intravenous phenytoin by 15% and increases the apparent elimination half-life by 27% (Gugler & Jensen, 1985). In our study, although the mean apparent elimination half-life of phenytoin was increased in 8 of the 10 subjects whilst on omeprazole the change was not sufficient to reach significance.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Previous work, however, suggests that omeprazole could significantly interfere with the hepatic elimination of phenytoin: omeprazole 60 mg day-' impairs antipyrine clearance by 14%, although no significant change occurs with a lower dose (30 mg day-1) (Henry et al, 1984); and omeprazole (40 mg day-1) decreases the clearance of intravenous phenytoin by 15% and increases the apparent elimination half-life by 27% (Gugler & Jensen, 1985). In our study, although the mean apparent elimination half-life of phenytoin was increased in 8 of the 10 subjects whilst on omeprazole the change was not sufficient to reach significance.…”
Section: Discussionmentioning
confidence: 94%
“…It is effective in healing peptic ulcers at doses ranging from 10 mg to 60 mg per day (Prichard et al, 1985). A recent study has shown that omeprazole impairs the plasma clearance of both diazepam and phenytoin when given intravenously (Gugler & Jensen, 1985), possibly through inhibition of hepatic cytochrome P-450 mono-oxygenases, there being evidence that the benzimidazole moiety binds to microsomal cytochrome P-450 (Dickens & Bridges, 1982), and that omeprazole impairs antipyrine clearance in a dose-related manner (Henry et al, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…The resulting pro longed reduction in gastric acidity has been useful in the therapy of gastroesophageal re flux disease and in hypersecretory condi tions such as the Zollinger-Ellison syndrome. Early studies in humans showed that the administration of omeprazole was associ ated with prolongation of the half-lives of aminopyrine [1], diazepam and phenytoin [2,3], Omeprazole has also been shown to significantly depress the peak cortisol re sponse 1 h after treatment with ACTH in male volunteers [4], Additionally, it has been reported that omeprazole inhibits 7-ethoxycoumarin de-ethylation in vitro in both hu man [5] and rat [6] liver microsomes.…”
mentioning
confidence: 99%
“…Omeprazole, for instance, dose-dependently inhibits the hepatic elimination of diazepam [3,4], carbamazepine [5], possibly of phenytoin [3, [6][7][8], and to a small extent that of aminopyrine [9] and (R)-warfarin [10]. It also induces the expression and activity of cytochromes P450 lAl/2 [11][12][13][14], inhibits adrenocortical steroidogenesis [15] but fails to alter 2-hydroxylation of oestradiol in males [16].…”
Section: Introductionmentioning
confidence: 99%
“…While antipyrine clearance is slightly reduced with omeprazole [9] and slightly increased with lansoprazole [19], theophylline clearance is marginally increased with both drugs [20,21].…”
Section: Introductionmentioning
confidence: 99%